Law enforcement and eradication of criminal actions of narcotics in Pohuwato district area - Herlina Sulaiman; Muhammad Rizal Lampatta (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
Narcotics, as one of the main enemies of the Indonesian nation, has reached an alarming stage. The targets of the dealers are not only adults and the economic community and above, but have also reached children and the economic community downward. This of course requires the role of law enforcement officials in enforcing and eradicating narcotics crime. This study aims to identify and analyze about eradication and law enforcement and its obstacles against narcotics crime in Pohuwato Regency